The subversive strategies of populist power: on the emancipatory potential of citizenship education and the public sphere - Maślanka, Tomasz (Adult Education Discourses, 2025)
In this article, the author presents various strategies employed by populist power that lead to ontological and axiological exclusion and the structural blockage of the communicative dimension of the public sphere as a civil space for dialogue. The article refers, among other ideas, to Jürgen Habermas’s normative theory of the public sphere and Chantal Mouffe’s concept of agonistic pluralism to show the threats to democracy, public order, and the functioning of civil society that result from the new forms and mechanisms of symbolic power and that produce polarization, stigmatization, and the exclusion of different ways of defining reality. The author presents the main assumptions of citizenship education in regard to forming social consciousness, developing critical thinking skills and other civic competencies, and forming habits of active participation in public life, all of which can influence the structure and key functions of the public sphere and unlock its emancipatory dimension. The author tries to show that countering the strategies of polarization and ontological exclusion used by populists requires citizenship education, understood as a certain normative project. The article outlines a perspective that could provide an opportunity at the present time for depolarization and the restoration of mutual respect between social groups with antagonistic worldviews and axiologies.